Gheorghe Moroșanu - On the occasion of his 70th birthday - PETRUȘEL, Adrian (Studia Universitatis Babeș-Bolyai Mathematica, 2021)
Gheorghe Moro¸sanu was born on April 30, 1950, in Darabani, Boto¸sani County, Romania. After a 12-year period of education, from primary to high school (1957-1969), in 1969, Gheorghe Moro¸sanu started studying Mathematics at ”Alexandru Ioan Cuza” University in Ia¸si, Romania. In 1981, under the joint supervision of Adolf Haimovici and Viorel Barbu, he obtained his Ph.D. in Mathematics with a dissertation entitled Qualitative Problems for Nonlinear Differential Equations of Accretive Type in Banach Spaces.